Temporal and spatial characterization of turbulent structures in liquid phase using POD technique - Munir, S. (American Institute of Physics Inc., 2015)
The temporal and spatial structures of turbulent liquid phase (water) in pipelines were investigated. Two cases were considered one single liquid phase flow at 80 l/m, second slugy part of slug flow by introducing gas (compressed air) at 60 l/m while keeping liquid flow rate same. Particle image velocimetry (PIV) was used for quantitative measurement of two-dimensional instantaneous velocity of liquid phase. The overall effect of coherent structures on the dynamics of flow in liquid phase for both cases were studied by proper orthogonal decomposition (POD). POD technique was able to identify the structures and characterize them. Spatial and temporal modes were achieved for both cases. The dynamics of flow structure were quite changed with the introduction of gas phase for case II. For case I, the first two spatial modes contained 40 of the energy while for case II only first spatial contained the maximum energy. FFT analysis of temporal modes showed that the first temporal mode for case I has frequency 4.617 while for case II the first temporal mode has frequency 4.64Hz. Â© 2015 AIP Publishing LLC.